2019
DOI: 10.1111/jfbc.12988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turmeric ( Curcuma longa) Extract in streptozocin‐induced diabetic model

Abstract: Herbal remedies have been used for centuries to ameliorate complications of diabetes mellitus (DM). The aim of this study is to compare the effects of the oral curcumin supplement versus parenteral administration of turmeric extract on diabetic complications in a streptozocin (STZ) diabetic model. STZ DM rats received low and high doses turmeric extract intraperitoneally as well as oral curcumin. Curcumin and turmeric extracts significantly reduced blood glucose and creatinine levels, but not urea, and caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…At least in part, this effect could be related to the positive correlation between the OSTT and glucose diffusion; as well as, to the negative correlation for α‐glucosidase. Additionally, our results are in agreement with studies showing that curcumin decreases glucose concentrations (Essa et al, 2019; Jaafari, Abnous, Mobarhan, & Oskuee, 2016; Xie, Wu, Shen, Li, & Wu, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…At least in part, this effect could be related to the positive correlation between the OSTT and glucose diffusion; as well as, to the negative correlation for α‐glucosidase. Additionally, our results are in agreement with studies showing that curcumin decreases glucose concentrations (Essa et al, 2019; Jaafari, Abnous, Mobarhan, & Oskuee, 2016; Xie, Wu, Shen, Li, & Wu, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…It has been showed that liver triacylglycerol and cholesterol concentrations were considerably less in rats fed curcumin than in control animals [36]. Relative growth rate = [(W2 -W1) x100]/ [1/2 (W2+W1)] Whereas: W1= the initial weight, and W2 = the final body weight Performance index = (final live body weight (kg)/ feed conversion ratio) x 100 [19].…”
Section: Some Blood Parametersmentioning
confidence: 99%
“…And it has been found the effect to decrease the cholesterol level in humans [17] and in rabbits which suggested the role to manage the cardiovascular disease [12]. Furthermore, it has been indicated the beneficial role of turmeric extract in other diseases and disorders including obesity, diabetes and liver disease [18][19][20][21]; whereas to the anti-inflammatory effects the immune system [22][23][24]. So, this study investigates the effect of the inclusion of turmeric powder in diets on fattening rabbits and some blood biochemical traits.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the therapeutic use of natural products with antioxidative and anti‐inflammatory potentials would be a good candidate for the treatment of diabetes and AD. Interestingly, the use of natural products, especially from plants in the management of diseases, has gained attention in recent times, partly because they are presumed to be less toxic, readily available, affordable, and with milder adverse side‐effects unlike synthetic drugs such as acarbose (Ekor, ; Essa et al, ).…”
Section: Introductionmentioning
confidence: 99%